The Euromarket in the face of change - Wolfgang Gerhardt (Intereconomics, 1985)
Financial innovations are currently displacing traditional methods of Euro-currency financing, while in Germany and Japan there is talk of establishing international free banking zones along American lines. What are the reasons for these developments and how are they affecting the Euromarket?
Keywords: 330; International Banking Zones